Impulsive consumption and reflexive thought: Nudging ethical consumer behavior - Leonhard K. Lades (Max Planck Institute of Economics, 2012)
The paper deals with impulsive consumption and highlights the roles that cognitive and motivational aspects of reflexive thought (namely self-control and self-image motives, respectively) play in intertemporal decisions. While self-control inhibits individuals from consuming impulsively, self-image motives can induce impulsive consumption. Based on recent neuroscientific findings about 'wanting'-'liking' dissociations, the paper presents a potential motivational mechanism underlying such impulsive consumption decisions. Utilizing the knowledge of this mechanism and acknowledging both cognitive and motivational aspects of reflexive thought, the paper expands on three libertarian paternalistic means to foster an ethical way of impulsive consumption: strengthening willpower, reducing impulsive desires to consume, and guiding impulsive behavior in ethical directions by making salient certain self-images that favor ethical consumption.
Keywords: B; B52; D03; D91; K2; Q3; 330; Impulsive Consumption; 'Wanting' versus 'Liking'; Ethical Consumption; Libertarian Paternalism; Konsumentenverhalten; Motivation; Persönlichkeitspsychologie; Kognition; Meritorisches Gut; Theorie